2018
DOI: 10.3389/fphys.2018.01471
|View full text |Cite
|
Sign up to set email alerts
|

Combined Aerobic and Resistance Exercise Training Improve Hypertension Associated With Menopause

Abstract: The prevalence of hypertension sharply increases in menopausal women. Recent studies have demonstrated that aerobic or resistance training may help control hypertension. In this study, we report that combining aerobic and resistance training may provide an effective therapeutic approach for hypertension control, attenuating inflammation and oxidative stress in ovariectomized rats. Female Wistar and spontaneous hypertensive rats (SHR) were distributed into four groups: sedentary control (C), sedentary hypertens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 41 publications
5
42
0
2
Order By: Relevance
“…As judged from the comparison of the TRAINED and SED groups, the practice of combined aerobic-resistance exercise training also had anti-inflammatory actions, since the TRAINED group presented lower serum levels of proinflammatory cytokines than the SED group. Similar to our results, some authors have reported that combined aerobic-resistance exercise training improves the inflammatory status [4446]. It is reasonable to hypothesize that these anti-inflammatory effects may be associated with the antioxidant effects of exercise training observed here, since the relationship between chronic inflammatory processes and oxidative stress, especially in aging, is well-known [47, 48].…”
Section: Discussionsupporting
confidence: 91%
“…As judged from the comparison of the TRAINED and SED groups, the practice of combined aerobic-resistance exercise training also had anti-inflammatory actions, since the TRAINED group presented lower serum levels of proinflammatory cytokines than the SED group. Similar to our results, some authors have reported that combined aerobic-resistance exercise training improves the inflammatory status [4446]. It is reasonable to hypothesize that these anti-inflammatory effects may be associated with the antioxidant effects of exercise training observed here, since the relationship between chronic inflammatory processes and oxidative stress, especially in aging, is well-known [47, 48].…”
Section: Discussionsupporting
confidence: 91%
“…NOX activity in the sample was determined by the production of superoxide, using 50 mM phosphate buffer containing 2 mM EDTA and 150 mM sucrose, 1.3 mM NADPH, and 10 μ L of sample. Superoxide production was expressed as nmol/min/mg protein [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…It is well known that acute exercise activates the sympathetic drive and generates reactive oxygen species (ROS) [15,16]. However, regular (chronic) exercise training improves cardiovascular autonomic control and up-regulates the antioxidants pro le in heart and kidney [17,18]. In this regard, our group has shown bene ts on cardiovascular and autonomic control parameters in healthy females [19] as well as in male rats [20] after a protocol of moderateintensity aerobic exercise training.…”
Section: Introductionmentioning
confidence: 90%